Evaluating the adoption of handsearching, citation chasing, and screening tools in education research: a survey study - Zhang, Qiyang; Pellegrini, Marta; Marsili, Francesco; Neitzel, Amanda (Frontiers in Research Metrics and Analytics, 2024)
IntroductionThe rapid development of software tools to assist systematic reviewers has led to varying degrees of adoption and selection among researchers. However, the actual usage patterns of these tools, their preferred features, and the criteria for selecting the most suitable tools remain unclear.MethodsTo understand these aspects, we collected 175 responses from researchers across different continents.ResultsIn terms of handsearching, despite new tools developed, our findings reveal that manual handsearching remains prevalent among more than half of the participants. Databases are the most popular tools for citation searching, followed by citation management tools and spreadsheets. This reliance on citation management tools and spreadsheets is concerning as they are not specifically designed for systematic reviews. The primary factors influencing tool selection are the research environment and ease of use. Barriers stopping researchers from adopting alternative tools include limited awareness, challenges in learning new tools, and the financial costs associated with acquiring licenses. Moreover, researchers located in Europe show greater familiarity with a wider range of tools compared to their North American counterparts.DiscussionThis preregistered study contributes valuable insights into the tool usage patterns of education researchers, emphasizing the importance of promoting awareness and facilitating the broader adoption of existing tools.